Kualitas Laba Dan Faktor-Faktor Yang Berpengaruh (Studi Kasus Pada Perusahaan Manufaktur Tahun 2017-2019) - Putu Kepramareni; Sagung Oka Pradnyawati; Ni Nyoman Alit Swandewi (Universitas Warmadewa, 2021)
Earnings quality is the ability of earnings in financial statements to explain the actual condition of the company's earnings as well as being used in predicting future earnings. Quality earnings show optimism that can predict future profits. This study aims to examine and obtain empirical evidence about the effect of capital structure, profitability, firm size, liquidity and investment opportunity set (ios) on earnings quality in manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019. The sample selection was done by purposive sampling method. The data analysis technique used in this research is multiple linear regression analysis, it is obtained as many as 65 manufacturing companies as the research sample with a total of 165 manufacturing companies observed. The population of the data in this study are all manufacturing companies listed on the Indonesia Stock Exchange for the period 2017-2019, with a total of 195 manufacturing companies. The results showed that the capital structure variable had a negative effect on earnings quality, while profitability, firm size and liquidity had a positive effect on earnings quality, and the investment opportunity set (IOS) had no effect on earnings quality.